2019
DOI: 10.1002/er.4715
|View full text |Cite
|
Sign up to set email alerts
|

A steel slag–derived Boudouard reaction catalyst for improved performance of direct carbon solid oxide fuel cells

Abstract: Summary Solid oxide fuel cells (SOFCs) can directly utilize solid carbon as fuel by integrating with the reverse Boudouard reaction in the anode chamber. Efficiency of the Boudouard gasification of solid carbon fuel is one of the crucial factors influencing the performance of direct carbon SOFCs (DC‐SOFCs). In this paper, a novel Boudouard reaction catalyst derived from steel slag was first introduced into DC‐SOFCs for improving the electrochemical performance. The catalytic activity of the steel slag was acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(246 reference statements)
0
7
0
Order By: Relevance
“…Our previous study revealed that the SS catalyst with active components of CaO and Fe 2 O 3 have catalytic activity on biomass pyrolysis, reforming reactions, and the Boudouard reaction (Table 3). 40 Promoted by the catalyst, biomass can produce more small molecule gas (CO, H 2 ), which will reduce the anode concentration polarization and significantly improve the output performance of the cell. Wang et al reported that when the cell configuration, anode materials and test conditions are identical, the anode concentration polarization is the main factor affecting the PPD, and the concentration polarization is determined by the concentrations of anode combustible gases 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study revealed that the SS catalyst with active components of CaO and Fe 2 O 3 have catalytic activity on biomass pyrolysis, reforming reactions, and the Boudouard reaction (Table 3). 40 Promoted by the catalyst, biomass can produce more small molecule gas (CO, H 2 ), which will reduce the anode concentration polarization and significantly improve the output performance of the cell. Wang et al reported that when the cell configuration, anode materials and test conditions are identical, the anode concentration polarization is the main factor affecting the PPD, and the concentration polarization is determined by the concentrations of anode combustible gases 28 …”
Section: Resultsmentioning
confidence: 99%
“…The yield of the ATB char was 28%. In order to increase the gasification rate of the ATB sample, a mechanical mixing method was used to load the steel slag (SS)‐based catalyst of 50 wt% onto the ATB sample (ATB + SS) 40 . To prepare the ATB + SS sample, the catalyst was sieved through a 200 meshes sieve and then mixed with ATB powder in the mass ratio and ground in a mortar for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, designing cost-effective catalysts for the Boudouard reaction is highly urgent. Recently, strontium slag [32,83] and steel slag [87] have been used for constructing Boudouard reaction catalysts. In Han et al's study, the application of strontium slag-derived catalysts can improve the DC-SOFC output from 189 to 248 mW•cm −2 at 850 • C, and the improved system attains a fuel utilization of 25.6% [83].…”
Section: Fuel Cellsmentioning
confidence: 99%
“…The catalyst must be pretreated with acetic acid, and without this pretreatment, carbon deposition results much more limited. This appears a limitation for a continuous process, but there are many alternative catalysts active in the Boudouard reaction, which were not explored by Luc et al [42] limiting their analysis to Fe and Fe2O3, and to 500°C as operational temperature, using as model for the study the direct carbon solid oxide fuel cells, but which typically operate at higher temperatures [48][49][50]. Note that the Boudouard reaction can be significantly promoted using microwaves [31].…”
Section: Introductionmentioning
confidence: 99%